American Metropolitics : The New Suburban Reality - Orfield, Myron (Book collections on Project MUSE., 2011)
In 1998, Myron Orfield introduced a revolutionary program for combating the seemingly inevitable decline of America's metropolitan communities. Through a combination of demographic research, state-of-the-art mapping, and resourceful, pragmatic politics, his groundbreaking book, Metropolitics, revealed how the different regions of St. Paul and Minneapolis pulled together to create a regional government powerful enough to tackle the community's problems of sprawl and urban decay. Orfield's new work, American Metropolitics, applies the next generation of cutting-edge research on a much broader sc.